Human diseases and conditions : supplement 1 : behavioral health - Izenberg, Neil; Dowshen, Steven A. (New York : Charles Scribner's Sons, 2001)
Present articles dealing with all kinds of diseases and disorders, from acne and brain tumor to tabacco-related diseases and yellow fever
'Published in association with the center for children's Health Media, the Nemours Foundation.'
Includes bibliographical references and index
Keywords: Medicine, popular -- encyclopedias; Diseases -- encyclopedias; Health -- Encyclopedias